Konsep Dasar Kesehatan Mental(Pengertian, Prinsip-Prinsip, Fungsi Mental Hygiene) - Ardiva Morlindah Tripertiwi (Yayasan Almahmudi Bin Dahlan, 2025)
Nowadays we often find individuals who experience anxiety disorders, fear and other negative feelings, this condition certainly has a cause and there is a root cause for that in this article the author will discuss what is the meaning, principles, and functions of mental health. Where the hope is that through this article the reader can take advantage of themselves so that they can understand the importance of mental health to live their daily lives. Subjective factors in determining the concept of healthy and sick are contained in the understanding of health in Law No. 9 of 1960 concerning the principles of health, it is stated that